THE RELATIONSHIP BETWEEN ANXIETY LEVELS THROUGH SLEEP QUALITY OF WIJAYA HUSADA NURSING STUDENTS: HUBUNGAN TINGKAT KECEMASAN DENGAN KUALITAS TIDUR PADA MAHASISWA PROGRAM STUDI S1 KEPERAWATAN STIKES WIJAYA HUSADA BOGOR - Julianto Julianto Laia (Wijaya Husada, 2019)
Sleep quality is one of basic componen human needs. When the basic human need disturbed it willaffect to activity, work, and health status. Sleep quality can be influenced by many factors such asanxiety level. This Research is aims to find the correlation between anxiety level with sleep quality of Bachelor Nursing Student Program in STIKes Wijaya Husada Bogor. This Research is used Descriptiv Analitik Kualitatif design with approach Cross Sectional. The population studied is Bachelor Nursing student which amounts 290 person. To get sample is using technique Simple Random Sampling with formulas Slovin which amount 168 respondent. The instrumen of this research is Pittsburgh Sleep Quality Index and Hamilton Anxiety Rating Scale, and then data analysis using chi square test. The result from this research show from 168 responden, there are 73 responden (43,5%) have sufficient anxiety level with bad sleep quality amount 51 responden (46,8%). Its obtained P value = 0,038 with value significance is < 0,05. It means Ho is refused and Ha is accepted. And based on result, it can be concluded there is significant correlation between anxiety level with sleep quality of student S 1 Nursing Program in STIKes Wijaya Husada Bogor 2016. And the results obtained by analysis of the value OR 2,492,its mean a person who have a high anxiety level can get a bad sleep quality 2,492 or 2 times greater than a person who have a low anxiety level. There is a correlationbetween anxiety level with sleep quality of Bachelor Nursing Student Program in STIKes Wijaya Husada Bogor It is expected to institutions can make subtlety that can make anxiety level decline so the sleep quality student can be better.